A case study cost modelling of regulatory alternatives to mitigate the mobile network coverage and capacity problems in rural areas - Mårten Sundquist; Jan Markendahl (International Telecommunications Society (ITS), 2015)
Despite a continued build-out of mobile networks, both mobile network coverage and capacity problems in rural areas are increasing. This counterintuitive situation is due to the exponential growth in mobile data usage, the long inter-base station site distance in rural areas and the increasing requirements on ubiquitous coverage not only for humans but also for the Internet of Things. With today's communication systems and business models, it is not commercially viable to solve the problems by the MNOs (Mobile Network Operators) alone. The paper aims instead of studying the different regulatory strategies available for NRAs (National Regulatory Agencies) to improve the situation. The main focus and contribution of the paper is to make a cost modelling of the main regulatory solutions available to improve the coverage and capacity in rural areas. An overall cost benchmark is then made, where the relative cost for network operators, affected end-users and the public sector is displayed.
Keywords: 330